Osteonecrosis of the jaws associated with the use of bisphosphonates: literature review (Research, Society and Development, 2022)
Osteonecrosis of the jaws is a disease due to the presence of necrotic bone, which is exposed in the maxillofacial region, with resistance for more than eight weeks, in patients who use bisphosphonates or anti-resorptive or anti-angiogenic therapies. Thus, the present study contains a literature review, exposing the main conversational factors of osteonecrosis in bisphosphonate users. For this, a bibliographic survey was carried out, with databases from PubMed, SciELO, LILACS and BIREME, between the years 2016 to 2021. With the studies, it was observed that, although there is no definitive protocol for the treatment, the action of preventing and carrying out an early diagnosis reduces the death of patients, with the adoption of correct therapies, which must be carried out with the assistance of a dentist, for an evaluation of each case, providing an effective dental conduct, for all treatments.